Understanding South African xenophobia through the prism of J. M. Coetzee's Summertime Scenes from a provincial life - Zajec, Polona (Acta neophilologica, 2017)
The xenophobic violence and discrimination that greets African migrants in post-apartheid South Africa highlights a social and political issue that threatens the idea(l) of the open pan-African society. The article looks at this xenophobia through the lens of J. M. Coetzee fictionalized memoir Summertime "Scenes from a Provincial Life" and tries to develop a new understanding of South Africa's relationship to the African "other" or to the "other" Africa, relevant not only in the context of postcolonial studies but also in a more global perspective on social and cultural responses to processes of migration.
Keywords: Coetzee, J. M., 1940-; human migration; Južnoafriška republika; ksenofobija; Literarne študije; migracije; post-apartheid; postkolonialne študije